Are you Prepared to Take the Risk: Extending Governance for Perioperative Roles. Issue 9 (September 2015) - Quick, J; Hall, S; Jones, A
In the 25 years since the Oxford Heart Centre in England appointed the first British nurse to be formally trained as a non-medically qualified surgical assistant, the number of nurses and allied health professionals (AHPs) undertaking advancing surgical roles has increased in order to backfill the deficit of a surgical workforce(Quick and Hall 2014). Despite initial concerns over nurses and AHPs undertaking roles and responsibilities which were previously performed solely by doctors, the role of non-medical surgical assistants has been shown to maintain surgical services, provide an additional career route for nurses, and enhance patient care (Abraham 2011, Quick 2013, Jones et al 2012). In the early days however, a lack of role specific regulation, practice guidelines and a variety of educational standards led to variances in job titles and role responsibilities for nurses and AHPs performing surgical assistance (Box 1).